Bio-electrical impedence plethysmography-designing an efficient non-invasive electrode for cardiac rate analysis - Umer, Daniya; Ellahi , Ghanwa; Ellahi , Warda; Ayub , Saba; Mohy Ud Din , Zia (International Journal of Endorsing Health Science Research, 2013)
Cardiac rate analysis is constituted as one of the most essential parts of physiological patient monitoring. In this research paper, it has been investigated that electrical impedance plethysmography is the most conducive technique for this purpose. It is perceptible that the artery closest to the epidermis will generate a precise reading and for that purpose, we have designed an efficient non-invasive model based on a tetra-electrode setup placed in contact with the stratum corneum of the skin. By varying electrode size and the distance between the electrodes we can efficiently judge the point where the electric field reaches the artery. The simulation of this model is carried out by Comsol Multiphysics.